Entitas Bisnis Pondok Pesantren : Antara Nilai Barokah Dan Going Concern - Malia, Evi; Kusuma, Nailah Aka; Uyun, Jamilatul (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2022)
The purpose of this research is to find out how business entities owned by boarding schools maintain their existence. The method in this study is to use qualitative research method with interpretive approach. The result of this study is that the value of barokah is directly proportional to the principle of going concern (Continuity of business) in accounting. In the business entity pondok pesantren barokah interpreted if the system is run in accordance with the rules and standards that apply generally, does not deviate from religious teachings, honest and give zakat in accordance with nishab, then the business carried out will be sustainable. It supports the concept of going concern that the company will continue to operate for a long period of time if supported by financial and non-financial factors that run balanced and well. This research contributes to maintaining the value of religion in a kaffah, because if religious values are well practiced in the business world then it will synergize with the sustainability of the business itself. The implication of this research is as an input for businesses to include religious values as the basis of business behavior.